MEMBANGUN PILAR KEILMUAN DALAM PILIHAN KEAHLIAN KHUSUS BAGI MAHASISWA PENDIDIKAN LUAR BIASA - Hermanto, Hermanto (Dinamika Pendidikan, 2009)
The students awareness  of special education 10 comprehend all subject and skill demand science the first  lecture is the important and urgent thing, Student's awareness  to the professional scientific demand should be built early in the first semester. After comprehending  all scientific pillar. So, in further  to build the awareness to comprehend and master the specialty of scientific pillar s according to the optioned skill cluster such as specialty of blindness, deafness, mentally retarded, and etc. By comprehending and realizing all its scientific contruct since in the early lecture and mate ring those specialty pillars, it's expected that students can choose and plan the study well. Eventually,  the students lire able to find the contruction among subjects in bUilding skill, consequency. development  demand, and challenge of it's application in the field. So, it's very possible for special education student to be more professional after passing as the teacher's demand right now.   Keyword: Scientific Pillar, Skill of Special Education